Implication of Apoptosis for the Pathogenesis of Trypanosoma cruzi Infection - Decote-Ricardo, Débora; Nunes, Marise P.; Morrot, Alexandre; Freire-de-Lima, Celio G. (Frontiers in Immunology, 2017)
Apoptosis is induced during the course of immune response to different infectious agents, and the ultimate fate is the recognition and uptake of apoptotic bodies by neighboring cells or by professional phagocytes. Apoptotic cells expose specific ligands to a set of conserved receptors expressed on macrophage cellular surface, which are the main cells involved in the clearance of the dying cells. These scavenger receptors, besides triggering the production of anti-inflammatory factors, also block the production of inflammatory mediators by phagocytes. Experimental infection of mice with the parasite Trypanosoma cruzi shows many pathological changes that parallels the evolution of human infection. Leukocytes undergoing intense apoptotic death are observed during the immune response to T. cruzi in the mouse model of the disease. T. cruzi replicate intensely and secrete molecules with immunomodulatory activities that interfere with T cell-mediated immune responses and secretion of pro-inflammatory cytokine secretion. This mechanism of immune evasion allows the infection to be established in the vertebrate host. Under inflammatory conditions, efferocytosis of apoptotic bodies generates an immune-regulatory phenotype in phagocytes, which is conducive to intracellular pathogen replication. However, the relevance of cellular apoptosis in the pathology of Chagas’ disease requires further studies. Here, we review the evidence of leukocyte apoptosis in T. cruzi infection and its immunomodulatory mechanism for disease progression.